Abdominal Wall Defects in Greenland 1989–2015. Issue 11 (2nd May 2017) - Bugge, Merete; Drachmann, Gitte; Kern, Peder; Budtz–Jørgensen, Esben; Eiberg, Hans; Olsen, Britta; Tommerup, Niels; Nielsen, Inge‐Merete
Abstract : Background: In the last decades, an increasing rate of gastroschisis but not of omphalocele has been reported worldwide. Greenland is the world's largest island, but 80% is covered by an ice cap, it has a small population of around 56, 000 peoples (as of 2016). The occurrence of abdominal wall defects has never been investigated in Greenland. Methods: The present study is based on data retrieved from three nationwide and two local registries in the Greenlandic health care system over 27 years (1989–2015). Results: We identified 33 infants with abdominal wall defects born in the study time period. All cases were reclassified to 28 cases of gastroschisis, four cases of omphalocele, and there was 1 infant in the indeterminate group. The point prevalence at birth for gastroschisis increased significantly from 8 to 35 (average 10.7) per 10, 000 liveborn and ‐stillborn infants. Mothers below 20 years of age represented 23% of all cases and the prevalence for this group was 17 per 10, 000 liveborn and stillborn. Perinatal mortality for infants with gastroschisis was high (18%), and 1 year survival was 71%. For omphalocele, the prevalence varied from 8 to 11 per 10, 000 liveborn and stillborn infants. There was no increasing rate in the period, further highlighting an etiological difference between gastroschisis and omphalocele. Conclusion: This study confirms the increasing prevalence of gastroschisis in Greenland in the period from 1989 to 2015. The average was 10.7 per 10, 000 liveborn and ‐stillborn infants and, to the best of our knowledge, this is the highest prevalence ever reported. Birth Defects Research 109:836–842, 2017. © 2017 Wiley Periodicals, Inc.